2003
DOI: 10.1124/jpet.102.044628
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cytochrome P450 3A Protein Levels by Proteasome Inhibitors

Abstract: We have previously reported that CYP3A cross-links with polyubiquitinated proteins in microsomes from nicardipinetreated rats in a process that is distinct from classical polyubiquitination. To further examine the role of the proteasome in CYP3A degradation, we investigated the effects of proteasome inhibitors lactacystin, MG132, proteasome inhibitor 1, and hemin in primary cultures of rat and human hepatocytes. With the exception of hemin, these agents increased the total pool of ubiquitinated proteins in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…10C). 4 Together, our findings account for the profound CYP3A suppression by MG132 at 200 M concentrations detected by immunoblotting analyses (Zangar et al, 2003(Zangar et al, , 2008. They also rationalize the differential CYP3A4 suppression observed over 6 h between treatment with the NFB activation inhibitor 6-amino-4-(4-phenoxyphenyl-ethylamino)quinazoline (40%) and that with MG132 plus cycloheximide (75%) (Zangar et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…10C). 4 Together, our findings account for the profound CYP3A suppression by MG132 at 200 M concentrations detected by immunoblotting analyses (Zangar et al, 2003(Zangar et al, , 2008. They also rationalize the differential CYP3A4 suppression observed over 6 h between treatment with the NFB activation inhibitor 6-amino-4-(4-phenoxyphenyl-ethylamino)quinazoline (40%) and that with MG132 plus cycloheximide (75%) (Zangar et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…It is interesting to note that the CYP4A1/3 activities and protein expression levels in our study were unchanged, whereas Roberts (1997) showed that proteasome inhibitors could enhance CYP4A degradation in rat hepatocyte cultures. Studies by Zangar et al (2003) also showed that rat hepatocytes treated with proteasome inhibitors resulted in a decrease of CYP3A protein and mRNA levels. However, this is contrary to the CYP3A-ubiqutin-proteasome pathway, thus suggesting that CYP3A may be degraded by multiple pathways or proteasomes could be responsible for the degradation of proteins that suppress CYP3A expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of proteasome inhibitors to reduce P450 expression in vitro has been described previously (Zangar et al, 2003(Zangar et al, , 2008Anwar-Mohamed et al, 2008;Acharya et al, 2009), but the mechanism of this effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%